Imatinib plasma trough concentration and its correlation with characteristics and response in Chinese CML patients - Li Qiu-bai; Chen Chao; Chen Zhi-chao; Wang Hong-xiang; Wu Yan-lin; You Yong; Zou Ping (Acta Pharmacologica Sinica; Vol 31, No 8 (August 2010): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the pharmacokinetics of imatinib in Chinese chronic myelogenous leukemia (CML) patients. Methods: Fourty-six naïve Chinese CML patients treated with imatinib (400 and 600 mg daily, n=36 and 10, respectively) were recruited. The correlations of imatinib (400 mg) trough plasma concentrations (Cmins) with the patients' characteristics and responses were analyzed. Results: The overall mean (±SD, CV%) steady-state Cmins for imatinib at 400 mg (n=36) and 600 mg (n=10) daily was 1325.61 ng/mL (±583.53 ng/mL; 44%) and 1550.90 ng/mL (±462.63 ng/mL; 30%), respectively, and no statistically significant differences were found between them (P=0.267). At 400 mg daily, female patients had significantly higher Cmins than the male patients (P=0.048), and molecular responses were not correlated with imatinib Cmins, but they were correlated with time elapsed before imatinib therapy. Conclusion: The results suggest that Chinese CML patients have higher imatinib Cmins than their Caucasian counterparts and that the optimal initial imatinib dose for them requires further investigation.